PulSED: pulsed sonoelectrodeposition of fractal nanoplatinum for enhancing amperometric biosensor performance. Issue 11 (28th April 2016) - Taguchi, M.; Schwalb, N.; Rong, Y.; Vanegas, D. C.; Garland, N.; Tan, M.; Yamaguchi, H.; Claussen, J. C.; McLamore, E. S.
Abstract : A technique for deposition of fractal nanometal as a transducer in electrochemical sensing is described. The effect(s) of duty cycle and deposition time were explored, and two sensors are demonstrated. Abstract : For the first time, we combine pulsed electrodeposition with out-of-phase pulsed sonication for controlled synthesis of fractal nanoplatinum structures as the transducer layer in electrochemical sensing. We develop and test this technique, called bimodal pulsed sonoelectrodeposition (pulSED), as a simple approach for creating highly conductive transducer nanometals for use in sensing and biosensing. We first compared the efficiency of pulSED nanoplatinum to other pulsed electrodeposition techniques, and then explored the effect of duty cycle and plating time on electroactive surface area and nanoparticle size/morphology. The developed pulSED nanoplatinum displayed fractal features with a relatively homogenous size distribution (26.31 ± 1.3 nm) and extremely high electroactive surface (0.28 ± 0.04 cm 2 ) relative to other electroplating techniques (up to one order of magnitude higher). A high duty cycle (900 mHz) promotes formation of stable nanostructures (including fractal nanostructures) and reduces amorphous structure formation due to bubble cavitation and enhanced mass transport of metal ions to the electrode surface. To demonstrate the applicability of the pulSED technique, non-enzymatic and enzymatic sensors were developed for measuring hydrogen peroxide and glucose. The sensitivity for non-enzymatic peroxide sensing (3335 ± 305 μA cm −2 mM −1 ), non-enzymatic glucose sensing (73 ± 14 μA cm −2 mM −1 ) and enzymatic glucose biosensing (155 ± 25 μA cm −2 mM −1 ) was higher than, or similar to, other nanomaterial-mediated amperometric sensors reported in the literature. The pulSED technique is a one pot method for tunable synthesis of nanometal structures as a transducer layer in electrochemical sensing and biosensing that requires no precursors or capping agents, and can be carried out at room temperature with inexpensive hardware.